PENGAWASAN PELAYANAN PUBLIK OLEH OMBUDSMAN REPUBLIK INDONESIA (ORI) PERWAKILAN PROVINSI RIAU - Pramono, Widodo; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Based on the decision of the President of the Republic of Indonesia Number 44 Year 2000 on the National Ombudsman Commission stating that community empowerment through their participation in supervision will ensure the implementation of an honest, clean, transparent, free corruption and nepotism state. The Ombudsman as an oversighting independent institution is expected to remain in place for the administration of an Ombudsman State to move quickly towards a better government (Good Government).But the problems that occur that supervision has not been done effectively, which can be seen the implementation of supervision is still a passive and there are still many unresolved reports. This study aims to determine how the implementation of supervision of public services and factors - factors that influence the implementation of supervision by the Ombudsman of the Republic of Indonesia (ORI) Riau Province Representative. This research uses qualitative descriptive approach by using key method of informant with data collection technique using interview, observation, and documentation.The conclusion obtained from the results of this study indicates that the Oversight of Public Services by ORI Representative of Riau Province has not been effective, it can be seen from many reports from the unresolved community and ombudsman only give sanction in the form of suggestion or recommendation to institution that do deviation. Factors that affect, among others: human resources must continue to be added to the number and improve quality, placement of appropriate budget usage so that the supervision process can run well.Keywords: Supervision, Public Service, Ombudsman of the Republic of Indonesia